4.10 Problems 451 to 500

   4.10.1 \((-y(x)+2 x+3) y'(x)+2=0\)
   4.10.2 \((-y(x)+2 x+4) y'(x)-2 y(x)+x+5=0\)
   4.10.3 \((-y(x)-2 x+5) y'(x)-2 y(x)-x+4=0\)
   4.10.4 \((y(x)-3 x+1) y'(x)=2 (x-y(x))\)
   4.10.5 \((y(x)-3 x+2) y'(x)-3 y(x)-2 x+5=0\)
   4.10.6 \((4 x-y(x)) y'(x)-5 y(x)+2 x=0\)
   4.10.7 \((-y(x)-4 x+6) y'(x)=2 x-y(x)\)
   4.10.8 \((-y(x)+5 x+1) y'(x)-5 y(x)+x+5=0\)
   4.10.9 \(y'(x) (a+b x+y(x))+a-b x-y(x)=0\)
   4.10.10 \(\left (x^2-y(x)\right ) y'(x)+x=0\)
   4.10.11 \(\left (x^2-y(x)\right ) y'(x)=4 x y(x)\)
   4.10.12 \(y'(x) (y(x)-\cot (x) \csc (x))+y(x) \csc (x) (y(x) \cos (x)+1)=0\)
   4.10.13 \(x^2+2 y(x) y'(x)+y(x)^2+2 x=0\)
   4.10.14 \(2 y(x) y'(x)=x^3+x y(x)^2\)
   4.10.15 \((x-2 y(x)) y'(x)=y(x)\)
   4.10.16 \((2 y(x)+x) y'(x)-y(x)+2 x=0\)
   4.10.17 \((x-2 y(x)) y'(x)+y(x)+2 x=0\)
   4.10.18 \((-2 y(x)+x+1) y'(x)=-y(x)+2 x+1\)
   4.10.19 \((2 y(x)+x+1) y'(x)-2 y(x)-x+1=0\)
   4.10.20 \((2 y(x)+x+1) y'(x)-4 y(x)+x+7=0\)
   4.10.21 \(x^2+2 (y(x)+x) y'(x)+2 y(x)=0\)
   4.10.22 \((-2 y(x)+2 x+3) y'(x)=-2 y(x)+6 x+1\)
   4.10.23 \((-2 y(x)-4 x+1) y'(x)+y(x)+2 x=0\)
   4.10.24 \((6 x-2 y(x)) y'(x)=-y(x)+3 x+2\)
   4.10.25 \((2 y(x)+9 x+19) y'(x)-6 y(x)-2 x+18=0\)
   4.10.26 \(\left (x^3+2 y(x)\right ) y'(x)=3 x (2-x y(x))\)
   4.10.27 \(y'(x) (\tan (x) \sec (x)-2 y(x))+\sec (x) (2 y(x) \sin (x)+1)=0\)
   4.10.28 \(\left (e^{-x} x-2 y(x)\right ) y'(x)=2 e^{-2 x} x-\left (-2 y(x)+e^{-x} x+e^{-x}\right ) y(x)\)
   4.10.29 \(3 y(x) y'(x)+5 \cot (x) \cos ^2(y(x)) \cot (y(x))=0\)
   4.10.30 \(3 (2-y(x)) y'(x)+x y(x)=0\)
   4.10.31 \((x-3 y(x)) y'(x)-y(x)+3 x+4=0\)
   4.10.32 \((-3 y(x)-x+4) y'(x)-3 y(x)-x+3=0\)
   4.10.33 \((3 y(x)+2 x+2) y'(x)=-3 y(x)-2 x+1\)
   4.10.34 \((-3 y(x)-2 x+5) y'(x)-3 y(x)-2 x+1=0\)
   4.10.35 \((-3 y(x)+9 x+1) y'(x)-y(x)+3 x+2=0\)
   4.10.36 \((4 y(x)+x) y'(x)-y(x)+4 x=0\)
   4.10.37 \((4 y(x)+2 x+3) y'(x)=2 y(x)+x+1\)
   4.10.38 \((-4 y(x)+2 x+5) y'(x)=-2 y(x)+x+3\)
   4.10.39 \((-4 y(x)+3 x+5) y'(x)=-3 y(x)+7 x+2\)
   4.10.40 \(4 (-y(x)-x+1) y'(x)-x+2=0\)
   4.10.41 \((-4 y(x)-11 x+11) y'(x)=-25 y(x)-8 x+62\)
   4.10.42 \((5 y(x)+3 x+6) y'(x)=7 y(x)+x+2\)
   4.10.43 \((5 y(x)+7 x) y'(x)+8 y(x)+10 x=0\)
   4.10.44 \(\left (4 x^3+5 y(x)+x\right ) y'(x)+7 x^3+3 x^2 y(x)+4 y(x)=0\)
   4.10.45 \((6 y(x)-x+5) y'(x)=4 y(x)-x+3\)
   4.10.46 \(3 (2 y(x)+x) y'(x)=-2 y(x)-x+1\)
   4.10.47 \((7 y(x)-3 x+3) y'(x)+3 y(x)-7 x+7=0\)
   4.10.48 \((9 y(x)+x+1) y'(x)+5 y(x)+x+1=0\)
   4.10.49 \((-12 y(x)+5 x+8) y'(x)=-5 y(x)+2 x+3\)
   4.10.50 \((-16 y(x)+7 x+140) y'(x)+y(x)+8 x+25=0\)